Understanding compulsive behaviour in psychiatric disorders with a touchscreen rodent model of reversal learning - Rafter, M.D. (2017)
Behaviour is considered to be compulsive when it is performed automatically regardless of whether it results in deleterious consequences. Although most prominently associated with obsessive-compulsive disorder, compulsivity is also present in a host of other psychiatric disorders and likely represents a trans-diagnostic trait with shared dysfunctional circuitry (Gillan et al., 2016a). Despite this, no single treatment shows anticompulsive efficacy across disorders, and disorder-specific treatments are not particularly efficacious either (Grant et al., 2016). This may be because different circuitry parameters are disrupted in different disorders, but result in similar behavioural outcomes, therefore a treatment targeting one parameter will not alleviate dysfunction caused by alterations in a different parameter. This thesis investigates the circuitry of compulsivity by administering drugs that differentially target these parameters to rats undergoing associative learning tasks shown to be dependent on this neural circuitry.